Importance of motivational factors among students at the University of Iceland - Virbickaité, Darija, 1986- (2013)
Work motivation is a powerful tool that encourages employees to increase their performance at work. The more the employers know what factors motivates their employees the more they can enjoy increased work performance and better outcomes. The purpose of this study is to investigate what motivational factors are the most important among students at the University of Iceland at their present or future jobs because they are considered the future workforce. Moreover, it aims to explore whether the importance of motivational factors is affected by some demographic variables forming students’ behavior in ranking the importance of motivational factors. The research is a quantitative study where data was collected through online survey. The participants were students at the University of Iceland. Respondents were asked to rank ten motivational factors from the most important marked number one to the least important marked number ten. Results of the study show that students in the University of Iceland are most motivated by these factors: interesting work, good wages, job security and full appreciation of work done. Some minor differences were found in how sub-groups ranked motivational factors. However, the factors interesting work and good wages were the top priority to all the groups. This study could shed a light to employers, who will soon hire students from the University of Iceland, what students are expecting from their present or future jobs and create an attractive package to get the best specialists to their organizations.